(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
After several failed attempts at uprisings, unleashed after 1814 with the return of Fernando VII to his absolutist throne, in 1820 the liberal revolution would triumph again at the hands of Rafael del Riego, and with this, not only would the constitutional regime be reestablished, rather, the destinies of the overseas kingdoms would head towards their final break. The case of New Spain is significant because a year later Agustín de Iturbide took the rieguista model to achieve independence from the Mexican Empire, instituting a new way of negotiation: the pronunciamiento, which would be present throughout the Mexican 19th century.